Original paperIllness acceptance degree versus intensity of psychopathological symptoms in patients with psoriasis - Kostyła, Magdalena; Tabała, Klaudia; Kocur, Józef (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : Chronic inflammatory skin diseases such as psoriasis have undoubtedly a negative impact on the patients’ quality of life. Many of them may face various limitations in their psychosocial lives because of symptoms indicating the presence of psychopathological phenomena. Mental disorders in patients with skin diseases occur much more frequently than in the general population. Studies show that a considerable percentage (30-60%) of dermatological patients suffers from mental disorders (depressive and anxiety disorders being the most common). A person’s attitude towards illness, its acceptance, and also the recognition of its limitations may be of a great importance in the process of the disease control. Aim : To evaluate of the relationship between the illness acceptance degree, and the presence and intensity of psychopathological symptoms in patients with psoriasis. Material and methods : The research was conducted on a group of 54 people (23 men and 31 women), who were treated for psoriasis in the Department of Dermatology and Venereology, Medical University of Lodz and in the Department of Dermatology, Pediatric Dermatology and Oncology, Medical University of Lodz. The following research methods were used: a questionnaire prepared for the purpose of the research, Acceptance of Illness Scale (AIS) and Symptom Checklist (SCL-90). Results : It was found that there was a relationship between the skin illness acceptance degree and intensity of psychopathological symptoms in patients with psoriasis (negative correlations). Conclusions : The higher the degree of illness acceptance is, the better mental condition of patients with psoriasis is. The intensity of psychopathological symptoms is also affected by the duration of illness, other people’s attitude to the skin disease, age and education level of the patients examined.